ANALISIS HUKUM TERHADAP PERTANGGUNGJAWABAN HUKUM JASA PENILAI ASET - Emirzon, joni (Lampung University)
Institution asset appraiser is a professional business services to provide objective and independent assessment of the propert / assets. Appraisal services are particularly vulnerable to the game mark-up value of the property so that the necessary arrangements are obvious. Enterprises appraiser regulated in special regulations are still very few in number in addition to the Code of Conduct is dominated by services. Although the provisions of Code of Law. Civil and Penal Code may be used, but still required a variety of strict rules, such as in the areas of capital markets, banking, so as not to cause a variety of problems.Â Keywords: Asset Appraisal Services, Liquidation